The relationship between perceived service quality and perceived service value towards customer revisit intention / Philipia Jamine - Jamine, Philipia (2013)
Revisit intention has always been the important topic in competitive market of tourism destinations. However, it remains unclear why customers undertake repeat visit. Therefore, the main concern of this research is to figure out the factor of customers revisit intention to a hotel which is specifically focus on Perkasa Hotel Keningau. Specifically, this paper will use two factors which is perceived service quality and perceived service value which is chosen to be the factor of customer revisit intention. A field survey through questionnaires was conducted on 138 respondents. The results of this study indicated that perceived service value was the most important attributes and travel motives for revisit intention to Perkasa Hotel Keningau. It revealed that respondents were loyal to Perkasa Hotel Keningau and intent to revisit.